Profundización del olvido de las personas mayores institucionalizadas durante la primera pandemia del siglo XXI - Arcos Miranda, Evaristo (2021)
The disease caused by SARS-CoV-2 hit the world at the end of 2019, but it was in 2020 when it reached Latin America, and it did so severely. Faced with its imminent overflow, health systems prescribed confinement as a central measure to prevent its spread and, above all, to protect vulnerable populations. This article deals with this emerging issue, under the assumption that distancing measures would accentuate the family forgetfulness of the elderly, especially those who are in the last stage of life as inmates. From a qualitative approach, the impact of the phenomenon on the family relationships of the elderly in a residence located in Alto Balsas, Guerrero was analyzed, detecting that the calamity accentuated filial detachment towards them, and concluding that, regardless of the current socio-sanitary circumstances, the institutionalized experience an alarming stage of family forgetfulness.